Eco-Conversion of castor oil to Trimethylolpropane ester using non-and impregnated chicken egg shells (N-ICES) - Said, N.; M. V., Sivaguru; N., Ibrahim; Zulkafli, Hassan; Mohd Bijarimi, Mat Piah; Misebah, Fatimah A. (2018)
Castor oil as non-edible vegetable feedstock has high viscosity, which is found and distributed widely around the earth, has been becoming interesting issues for its conversion to trimethylpropane (TMP)-ester. The eco-conversion of castor oil was conducted in a bath stirrer flask via two-steps catalytic transesterification. Reactions of castor oil methyl ester (COME) and trimethylolpropane (TMP) were run under non- and impregnated eggshell (N-ICES) catalysts. Effects of catalyst loading, ratio of COME and TMP, reaction time and temperature were also observed. The highest TMP-ester conversion (98.90%) with triester composition (71.4%) was found by the COME and TMP ratio of 1:4, time of 3 h, temperature of 110°C and catalyst loading of 3 wt/wt%. Physico-chemical properties of resulted TMP-ester, mainly density of 924.70 kg/m3 and kinematic viscosity at 40°C of 65.77 mm2/s are commensurable with another renewable sources, catalysts and proposed lubricant standards. The impregnated chicken egg shell confers marvellous results compared non-impregnated shells performance, and the recyclable boths catalysts can be visualized for destiny lucrative engine oil.